Membumikan Platform Digital CANVA Untuk Mendesain Bahan Ajar Melalui Digitalisasi Guna Akselerasi Minat Baca di Dinas Pendidikan Kabupaten Bekasi - Syahyuri Syahyuri; Nico Harared (Jurnal Ilmiah Pangabdhi, 2022)
The aim of this community service activity is to provide socialization of the use of the Canva application; to help the teachers in the 5.0 industrial revolution era, especially in the process of designing online teachingmaterials; to provide new teaching material design to give an experiences to teachers which in the end get convenience in online learning teaching materials. This activity uses the Canva application. The method usedintroducting, training/practice, mentoring and evaluating. By using the Canva application, the teaching material design process is considered to be more attractive and attractive to students and greatly facilitatesthe industrial era 5.0 teacher. From these results, it can be concluded that there is still a need for intensive socialization and training to teachers regarding the use of the Canva application as an effective and efficientevaluation application for teachers. The introduction of this application is expected not only to be introduced to teachers in SMPN 1 Bojongmangu, but also to other cross-school teachers. However, of course this requirescooperation from various parties to realize this activity. Therefore, collaboration with related parties is part of the next stage plan for the implementing team in order to introduce this Canva application in every school that needs it.